Controlling the photophysical properties of ionic transition-metal complexes through various counterions. Issue 88 (21st October 2022) - Xing, Guohui; Du, Tingchen; Liu, Shujuan; Ma, Yun; Zhao, Qiang
Abstract : This paper lists the counterions that can be used to tune the photophysical properties of ionic transition-metal complexes, and it also summarizes the advances towards their information encryption and anti-counterfeiting applications. Abstract : Ionic transition-metal complexes (iTMCs) with rich excited-state properties and excellent optical properties have attracted considerable attention from both the scientific and industrial community in recent decades. Controlling their photophysical properties is very important for realizing a diverse range of optoelectronic applications. Generally, the optical property modulation of iTMCs is achieved by covalent structural modification of their ligand skeleton. In this feature article, we highlight the full potential of the regulation of the optical properties of iTMCs through changing various counterions, which is demonstrated to be a facile and convenient method. This paper lists different counterions that can be used to tune the emission wavelengths, emission lifetimes, and response behaviors of iTMCs. This paper also summarizes the advances towards multi-level information encryption and high-level anti-counterfeiting applications. Moreover, the recent challenges relating to this topic are examined alongside various future directions. We anticipate that the research provided in this paper will assist in directing future analyses based on the regulation of the photophysical properties of iTMCs in a facile, reproducible, and convenient way.